1990
DOI: 10.1002/1097-0142(19901115)66:10<2082::aid-cncr2820661007>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

A phase i study of 4′-0-tetrahydropyranyladriamycin: Clinical pharmacology and pharmacokinetics

Abstract: A Phase I study of intravenous (IV) bolus 4'-O-tetrahydropyranyladriamycin (Pirarubicin) was done in 55 patients in good performance status with refractory tumors. Twenty-six had minimal prior therapy (good risk), 23 had extensive prior therapy (poor risk), and six had renal and/or hepatic dysfunction. A total of 167 courses at doses of 15 to 70 mg/m2 were evaluable. Maximum tolerated dose in good-risk patients was 70 mg/mz, and in poor-risk patients, 60 mg/m2. The dose-limiting toxic effect was transient nonc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Cardiotoxicity is the main adverse effect of THP. K S Sridhar et al had reported that there was no cardiotoxicity with a cumulative dose of 300 mg/m 2 THP 15 . The drug administration plan was based on the methods in literature and preliminary work of our group 16 , 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Cardiotoxicity is the main adverse effect of THP. K S Sridhar et al had reported that there was no cardiotoxicity with a cumulative dose of 300 mg/m 2 THP 15 . The drug administration plan was based on the methods in literature and preliminary work of our group 16 , 17 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with povidone‐iodine, IP pirarubicin at 50 mg/l for 15 minutes has no toxic effect on rat peritoneum, so local tolerance might be good in humans. The maximally recommended dose of pirarubicin given by the intravenous route is 60 mg/m 2 [39]. As most of the drug would be flushed after a 15 minute washing, a total dose of 100 mg pirarubicin diluted in 2 liters of a NaCl solution (final concentration 50 mg/l) could be used for peritoneal washing without the risk of adverse systemic effects.…”
Section: Discussionmentioning
confidence: 99%